2015
DOI: 10.1002/nop2.20
|View full text |Cite
|
Sign up to set email alerts
|

The repositioning of hospitalized patients with reduced mobility: a prospective study

Abstract: AimTo determine the frequency of patient repositioning across three consecutive nursing shifts (day, evening and night) and to identify predictors of repositioning frequency.BackgroundPatient repositioning is a frequently implemented pressure injury prevention strategy. Yet, little is known about how often it should be implemented, or the frequency of movement among hospitalized patients with reduced mobility.DesignAn observational prospective study.MethodsChart audits were used to gather clinical and demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
12
0
2
Order By: Relevance
“…In the present study 36.2 % patients were kept in propped up position to ease their breathing and SPO2 monitoring was done among 12.41%. Likewise study conducted in Australia found elevation of the head of the bed (1-45°) was the most frequently adopted position [15]. Present study also identified catheter care(6.9%), chest physiotherapy (3.7%), ambulation (8.6%), nasogastric tube feeding (1.2%), preoperative care (2.1%) and diabetic foot care(0.3%) as important nursing care provided to the patient.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In the present study 36.2 % patients were kept in propped up position to ease their breathing and SPO2 monitoring was done among 12.41%. Likewise study conducted in Australia found elevation of the head of the bed (1-45°) was the most frequently adopted position [15]. Present study also identified catheter care(6.9%), chest physiotherapy (3.7%), ambulation (8.6%), nasogastric tube feeding (1.2%), preoperative care (2.1%) and diabetic foot care(0.3%) as important nursing care provided to the patient.…”
Section: Discussionsupporting
confidence: 50%
“…This led to the conclusion that repositioning and positions used in the prevention of pressure ulcers is important [14]. A research study found that, patients were repositioned frequently during the day and evening and least at night time [15]. Pressure ulcers can predispose to a variety of complications that include bacteremia, osteomyelitis, squamous cell carcinoma, and sinus tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of a repositioning schedule was the most predominant PIP strategy used across all subgroups. Previous researchers have also shown that repositioning and mobilisation are often the most frequently used PIP strategies in practice . Yet, the most recent Cochrane review examining empirical support of repositioning highlights that there is still uncertainty about the ideal frequency and positioning to help prevent PIs .…”
Section: Discussionmentioning
confidence: 99%
“…Patient-handling activities, including patient turning, repositioning, and maneuvering of limbs, are performed as frequently as every 2 hr per patient (Latimer, Chaboyer, & Gillespie, 2015). Log rolling a patient onto their side using a draw sheet (Baptiste, 2011) is often identified as a challenging patient handling task (e.g., Vieira, Kumar, Coury, & Narayan, 2006).…”
Section: Introductionmentioning
confidence: 99%